Left-right asymmetries and exotic vector-boson discovery in lepton-lepton colliders - Montero, J. C. [UNESP]; Pleitez, V. [UNESP]; Rodriguez, M. C. [UNESP] (World Scientific Publishing, 2001)
By considering left-right (L-R) asymmetries we study the capabilities of lepton colliders in searching for new exotic vector bosons. Specifically we study the effect of a doubly charged bilepton boson and an extra neutral vector boson appearing in a 3-3-1 model on the L-R asymmetries for the processes e-e- → e-e-, μ-μ- → μ-μ- and e-μ- → e-μ- and show that these asymmetries are very sensitive to these new contributions and that they are in fact powerful tools for discovery of this sort of vector bosons.
Keywords: electron; elementary particle; mass; mathematical analysis; mathematical parameters; model